Development of Serdang Bedagai Saranjana Market Based on Sustainable Entrepreneurship: Synergy of Creativity, Marketing and Collaboration - Julianto Hutasuhut; Dini Dwi Wahyuningsih; Rany Aprilliana; Ananda Nirmala; Wanda Riana; Risdah Armayana (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2024)
This research aims to explore the development potential of Saranjana Market in Serdang Bedagai with a sustainable entrepreneurship approach that focuses on creativity, marketing, and collaboration. This research applied a qualitative descriptive research method. Data collection techniques through direct observation, interviews and documentation, and triangulation of Saranjana market activities. The research results show that the Saranjana market has great potential to become a culinary destination around the North Sumatra region because it has succeeded in increasing visitor interest. Saranjana Market managed by BUMDes Anugrah is also able to offer iconic products by combining Banjar's distinctive culture with local culture so that it becomes an attraction that can empower local Micro and Small Enterprises (MSEs). Some of the uniqueness of the Saranjana market is the innovation in the payment system that uses reed coins, the provision of photo spots with environmentally friendly views, and Banjar art performances. The synergy of creativity, marketing, and collaboration becomes a separate strategy designed by the Saranjana market manager to realize a sustainable business. The expected outcome of this research is that the Saranjana market can make a major contribution to improving the local economy and the welfare of the people of Serdang Bedagai through sustainable entrepreneurship. Keywords: Saranjana Market, Entrepreneurship, Sustainability.